Tenderness level and sensory analysis of buffalo meltique meat injected with various oils and papain - Yudhistira, Mohammad Ariq; Apriantini, Astari; Wulandari, Zakiah (Fakultas Peternakan, Universitas Padjadjaran, 2025)
Buffalo meat has a high nutritional value but tends to have a tough texture, making it less popular with consumers. Therefore, processing methods such as the meltique technique are needed to tenderize buffalo meat. The aim of this study was to evaluate the tenderness and sensory characteristics of buffalo meltique meat injected with different types of fats (beef tallow, Wagyu fat, coconut oil, and palm oil) combined with papain enzyme. The meltique technique, involving fat emulsion injection, enhances meat marbling and tenderness. Papain, a proteolytic enzyme derived from papaya extract, was applied to improve meat texture by breaking down myofibril proteins. The treatments were applied to sirloin cuts of buffalo meat and assessed through physical (tenderness and texture profile) and sensory (hedonic and quality) analysis. The design used in Texture analysis was a completely randomized design (CRD) with five treatment factors and three replications. Sensory test data were analyzed using the non-parametric Kruskal-Wallis test with the Mann-Whitney follow-up test. The results showed that all fat-injected treatments significantly improved meat tenderness (P<0.05) compared to control. Texture profile analysis showed a decrease in hardness, gumminess, and chewiness, particularly in treatments using Wagyu fat and palm oil. Hedonic tests showed no significant differences in aroma, color, and flavor across treatments, though texture was significantly preferred in fat-injected samples. Palm oil and Wagyu fat treatments resulted in higher consumer preference scores for texture and aroma. These findings suggest that combining fat emulsion injection and papain marination is an effective strategy to improve the tenderness and consumer acceptance of buffalo meat, offering a promising alternative to traditional meat products with lower cost and improved quality.